(untitled) (Asian Journal of Social Science Studies, 2022)
As one of the four prominent language skills, writing plays an indispensable role in international communication. Meanwhile, writing, particularly writing in English as a Foreign Language (EFL) has been broadly recognized as the most difficult part in EFL learning. In recent years, cognitive linguistics has provided a new perspective towards writing, proposing that there’s a close connection between the use of metaphor and EFL writing proficiency. To explore the relationship between the two, this study focused on the use of conceptual metaphor in college students’ EFL writing. Sixty English majors were invited to write a composition based on the given topic, and then the relationship between metaphoric competence and writing proficiency was investigated. The results showed that: 1) The majority of students are not good at using metaphors correctly and their metaphoric competence is at a relatively low level. 2) Students’ writing proficiency and metaphoric competence are correlated positively. This study revealed that more attentions should be paid to enrich students’ metaphoric knowledge and cultivate their metaphoric competence so as to improve their writing proficiency.